People with Disabilities in Emergency Housing: An Analysis of a National Administrative Database - Buchanan, Mary; Yu, Chang; Aspinall, Clare; Watt, Rosalie; Howden-Chapman, Philippa; Pierse, Nevil (International Journal on Homelessness, 2026)
People with disabilities experience barriers to safe, secure, and affordable housing and a heightened vulnerability to homelessness. This paper presents results of research using nationwide administrative data on the number of entries and length of stays in Emergency Housing for people with disabilities, compared to the general population. People can apply for Emergency Housing when they have nowhere else to stay. It is intended for short-term stays of seven days and is considered a form of homelessness in Aotearoa, New Zealand. Our results indicate that people with disabilities have stayed in Emergency Housing 6.2% more times, and for 2.6 days longer than the general population, on average. These results evidence that people with disabilities are significantly more likely to experience homelessness and face significant barriers to exiting homelessness. In conclusion, the housing system in Aotearoa NZ is disabling. People with disabilities are not currently adequately supported by the housing support structures that exist, and changes are needed, especially given the projected increase in need due to population ageing.